Effects of a Fluorescent Myosin Light Chain Phosphatase Inhibitor on Prostate Cancer Cells - Grindrod, Scott; Suy, Simeng; Fallen, Shannon; Eto, Masumi; Toretsky, Jeffery; Brown, Milton L. (Frontiers in Oncology, 2011)
Myosin light chain phosphatase is an enzyme important to regulation of cell cycle and motility that is shown to be upregulated in aggressive prostate cancer cells and tissue. We developed a fluorescent small molecule inhibitor of myosin light chain phosphatase (MLCP) using structure based design in recombinant PP1C. Several best fit compounds were synthesized and evaluated by their inhibition of MLCP/32P-MLC dephosphorylation, which resulted in the identification of novel MLCP inhibitors. Androgen dependent (AD) and independent (AI) prostate cancer cell lines were treated with the lead inhibitor resulting in decreased in growth rate, reduced DNA synthesis and G2/M cell cycle arrest. Moreover, AI cell lines showed an increased sensitivity to drug treatment having GI50 values four times lower than the AD prostate cancer line. This was reinforced by reduced BrdU DNA incorporation into AI cells compared to AD cells. Beta-actin disruption was also seen at much lower drug concentrations in AI cells which caused a dose dependent reduction in cellular chemotaxis of PC-3 cells. Since there are currently no clinical therapeutics targeting AI prostate cancer, MLCP represents a new target for preclinical and clinical development of new potential therapeutics which inhibit this disease phenotype.